Economic causes for the rise of populist and nationalist movements - Florian Dorn; David Gstrein; Florian Neumeier (EconPol Forum, 2024)
Radical parties and populists benefit from deteriorating macroeconomic conditions. For voters, the overall economic development appears to be more important than their actual personal economic situation. The most important economic factors explaining the rise of populism as well as the loss of trust in political institutions are a widening income gap between people and between regions, exposure to economic shocks, high economic uncertainty, and worries about the future. Financial and economic crises, high exposure to global trade competition, an accelerating structural transformation, and immigration are discussed as key factors for increasing economic uncertainty. Populists benefit from misperceptions about immigration and from perceptions of increasing economic risks, even if they differ from objective developments. To combat the rise in populism, democracies need to increase resilience. That requires well-designed welfare and education systems that shield citizens from the consequences of economic crises and ensure equal opportunities; sound and sustainable fiscal policy to be able to react to economic crises; and targeted economic policies and instruments to limit economic uncertainty during crises and to support regions and people that feel left behind.
Keywords: 330